Age-related features of blood cytokine contents in schoolchildren with gastritis and family predisposal to peptic ulcer disease - T. V. Polivanova; V. A. Vshivkov (Медицинская иммунология, 2025)
A number of studies have shown an association of gastritis symptoms with the levels of specific cytokines. However, some data observed are quite contradictory. Meanwhile, the peptic ulcer disease is known to be associated with unfavorable course of inflammatory processes in gastric mucosa, Moreover, the potential relationships between gastritis and blood cytokine levels in cases of familial predisposal to gastric ulcer have not been studied in children’s age. The aim of our study was to evaluate associations of cytokines in blood serum (IL-2, IL-4, IL-8, IL-18, IL-1β, IFNα, TNFα) with gastritis in the age groups of schoolchildren with a family predisposal to peptic ulcer disease. To this purpose, sophagogastroduodenoscopy with biopsies of gastric mucosa was performed in the children and adolescents (7 to 17 years old) with gastroenterological complaints. A total of 143 children, who had morphologically confirmed gastritis (Sydney classification), were under study, The presence of H. pylori was also determined by morphological technique. The levels of serum cytokines were measured by ELISA technique. The inter-group differences in laboratory parameters were assessed using the Mann–Whitney test. The study has shown that in schoolchildren with gastritis and reported family predisposal for peptic ulcer, the disease is associated with increased content of IFNα in blood, both in the older age group (p = 0.001) and among younger children (p = 0.023). Meanwhile, there were no differences in IFNα content between children with hereditary burden in different age groups. In addition, in older patients with familial burden, in contrast to younger children, an increased level of IL-2 (p = 0.001) and IL-4 (p = 0.015) was noted. Among children with family predisposal to peptic ulcer and H. pylori infection, no age-dependent differences in cytokine levels were found. No differences in the cytokine contents were revealed between schoolchildren of younger and older age with highly active gastritis (grade 2-3). IL-4 contents was the only exception which was higher in older schoolchildren with grade 1 gastritis (p = 0.049). The differences in blood cytokine profile in the schoolchildren may depend on family history of peptic ulcer disease, with some age-dependent characteristics, in particular, concerning IFNα and IL-4 levels.